NSCA's Guide to tests and assessments - Miller, T. A. (Science of Strength and Conditioning Series, 2012)
The text begins by laying the foundation of testing and data analysis and the methods of interpreting results and drawing conclusions. The chapters that follow include tests from the rudimentary (such as body composition and blood pressure measurement) to the more complex, such as lactate threshold testing and aerobic power. While all of these tests vary in complexity, this variability is not indicative of their degree of importance. For example, measuring body composition is a relatively simple task, yet its implications in athletic performance are incredibly profound. 1t is clear that excess fat can be deleterious to performance in sports that rely on speed, acceleration, and rapid changes in direction. Despite this, coaches will often spend long hours on speed training but pay little attention to measuring or improving body composition. We hope that this text not only serves as an instructional tool for the mechanics of conducting specific tests but that it also helps coaches determine which tests are appropriate for specific populations. For example, a test of aerobic power may be inappropriate for a thrower, whose performance relies primarily on strength and power. Conversely, a coach of a distance runner would benefit little from conducting agility testing on athletes. Therefore, you should not assume that you need to read this text cover to cover, nor should you assume all tests are appropriate for all athletes. As the field of strength and conditioning becomes increasingly sophisticated, so should the approach by which training programs are designed, implemented, and tested. A training program that lacks some type of progress tracking is grossly incomplete, yet it remains startlingly common among trainers of today. We are confident that this text will provide a solid foundation by which you can develop and implement your own testing and measurement programs, ultimately allowing you to grow as a coach and maximize the performance of your athletes.